Policy Brief - Survivorship is cancer survivorship the poor cousin of cancer control within the EBCP? - Régine Kiasuwa Mbengi; Gabrielle Schittecatte; Sofie Theys (BMC, 2024)
Abstract Background There is an increasing number of cancer survivors, including children, adolescents, young adults, individuals of working age, and the elderly, within the Belgian and European population. Yet, survivorship care and rehabilitation are often treated as an afterthought in care organisation. This not only directly affects the quality of life of survivors and carers, but also puts the sustainability of the healthcare and social security systems at risk. Methods We analysed the ongoing Europe Beating Cancer Plan (EBCP) to identify the actions supporting survivorship (care) developments, then compared their weight in the EBCP to the other domains of cancer control. Following this analysis, and comparison with related ongoing projects, and current infrastructure in Belgium, several unmet needs were identified. Conclusion To better address these unmet needs, we recommend that Belgium incorporates survivorship care and long-term follow-up in clinical guidelines and care pathways, and considers including indicators related to cancer survivorship in the planning and design of quality insurance schemes, including certification of comprehensive cancer centres. Furthermore, we suggest further investment and support for research and knowledge exchange in the field of survivorship.